Analysis of the Influence of Sleep Patterns, Emotional Stability, and Quality of Social Relationships on Mental Health of College Students in West Java - Emdat Suprayitno; Muhammad Rusdi; Supriandi Supriandi (Westscience Press, 2024)
This study investigates the interplay between sleep patterns, emotional stability, quality of social relationships, and mental health among college students in West Java. A sample of 250 students participated, and structural equation modeling (SEM) was employed to analyze the relationships. The results revealed significant positive associations between sleep patterns, emotional stability, quality of social relationships, and mental health. Specifically, better sleep patterns, higher emotional stability, and improved social relationships were linked to enhanced mental health. These findings underscore the importance of a holistic approach to mental well-being on college campuses. Practical implications for interventions targeting sleep hygiene, emotional regulation, and social connection initiatives are discussed. The study contributes to the understanding of factors influencing mental health in the unique cultural context of West Java.